Epidemiological profile of neonates submitted to surgery in a maternity in Teresina (Research, Society and Development, 2023)
Objective: To define the epidemiological profile of newborns admitted to surgeries in a reference maternity hospital in the city of Teresina-PI and the possible associated factors. METHODS: A retrospective, observational, cross-sectional, descriptive, qualitative and quantitative study was carried out on the epidemiological profile of neonatal surgeries at the reference Maternity, Dona Evangelina Rosa, from January 2019 to December 2021, with a data collection instrument by verification form containing the study variables: gender, hospitalization data, discharge data, gestational age at birth, mode of delivery, birth weight, APGAR score, presence of previous neonatal comorbidities at birth, presence of COVID19, type of surgical procedure and which therapy used, complications related to surgeries, therapeutic evolution and maternal history (age, serology, pathologies/complications that influenced the state of the NB, use of medication during pregnancy), exclusion chart. The results were analyzed according to the chi-square test and Fisher's exact test, (adopting the significance level of p